2012
DOI: 10.1021/ja3009693
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Characterization of the Smallest S-Nitrosothiol, HSNO; Cellular Cross-talk of H2S and S-Nitrosothiols

Abstract: Dihydrogen sulfide recently emerged as a biological signaling molecule with important physiological roles and significant pharmacological potential. Chemically plausible explanations for its mechanisms of action have remained elusive, however. Here, we report that H2S reacts with S-nitrosothiols to form thionitrous acid (HSNO), the smallest S-nitrosothiol. These results demonstrate that, at the cellular level, HSNO can be metabolized to afford NO+, NO, and NO– species, all of which have distinct physiological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
443
2
8

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 318 publications
(475 citation statements)
references
References 78 publications
22
443
2
8
Order By: Relevance
“…A number of in vitro studies in a marine echiuran worm and fish (67), mammalian heart (191,192), and RAW246.7 cells or liver homogenate (185) have shown that addition of H 2 S (as a sulfide salt or slow-releasing donor) to an NO donor (often sodium nitroprusside [SNP]) elicits a response in the tissue that is either greater than or different from the parent compounds. It has been proposed that this new signaling molecule is nitroxyl (HNO/NO -), a oneelectron reduced and protonated form of NO (191,192), and/ or a S-nitrosothiol (thionitrous acid [HSNO]) (40,185). The manner in which H 2 S and NO react has not yet been resolved, and a number of possibilities have been proposed (75).…”
Section: Reactions With No and Related Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of in vitro studies in a marine echiuran worm and fish (67), mammalian heart (191,192), and RAW246.7 cells or liver homogenate (185) have shown that addition of H 2 S (as a sulfide salt or slow-releasing donor) to an NO donor (often sodium nitroprusside [SNP]) elicits a response in the tissue that is either greater than or different from the parent compounds. It has been proposed that this new signaling molecule is nitroxyl (HNO/NO -), a oneelectron reduced and protonated form of NO (191,192), and/ or a S-nitrosothiol (thionitrous acid [HSNO]) (40,185). The manner in which H 2 S and NO react has not yet been resolved, and a number of possibilities have been proposed (75).…”
Section: Reactions With No and Related Compoundsmentioning
confidence: 99%
“…Reactions with nitrogenous compounds include an H 2 S reaction with S-nitrosols to produce thionitrous acid (HSNO) (8), an HSNO reaction with excess H 2 S to form HSSNO (SSNO -), which slowly decomposes to nitric oxide (NO), and interaction of H 2 S/HS -and NO as the former is a diamagnetic reductant or nucleophile, whereas NO is a paramagnetic free radical (43,75,86). However, one-electron reduction of H 2 S/HS -to produce the thiyl radical (HS ) or a one-electron oxidized species of NO, such as nitrite (NO 2 -), can react to produce HSNO/SNO - (40). HSNO/SNO -is reported to be further metabolized to NO + , NO, and NO -with a variety of distinct stimulatory functions, and since it can diffuse freely across membranes, it may facilitate transnitrosation of proteins (40).…”
Section: Reactions With No and Related Compoundsmentioning
confidence: 99%
“…Similarly, H2S can be stored in the form of sulfane sulfur and transported and released in response to a physiological stimulus [3]. A number of publications reported on the molecular interaction between H2S and NO or NO-donors [4][5][6][7][8][9][10][11][12][13][14], and H2S and NO were found to cooperatively regulate vascular tone by activating a neuroendocrine signaling pathway in which formation of nitroxyl (HNO) appears to play an important role [13]. Products of this H2S/NO interaction appear to have pronounced biological effects; however the nature of the reaction intermediates is currently unclear and many inconsistencies remain; for example, H2S donors were found to either potentiate or attenuate relaxation effect of NO donors in isolated aortic rings in vitro [15,16], or result in complete loss of vasodepressor activity in anesthetized rats [16].…”
Section: Introductionmentioning
confidence: 99%
“…H2S was shown to relax uterus from pregnant [17,18] and non-pregnant rats [19], and sodium nitroprusside (SNP) prevented H2S induced relaxation of rat uterus [20]. Thionitrous acid (HSNO) has been proposed to represent an important carrier of bioactivity of the interaction of S-nitrosothiols with H2S [10], but the evidence provided appears to be inconsistent with the known chemical properties of HSNO. Moreover, HSNO would be expected to rapidly react with excess sulfide to form other species; thus its biological effect would be very short-lived.…”
Section: Introductionmentioning
confidence: 99%
“…Although the direct observation of endogenously produced HNO in mammalian cells has remained elusive, CuBOT1 was also used to investigate the generation of HNO from the S-nitrosothiol GSNO and H 2 S. 17 Human umbilical vein endothelial cells (HUVECs) were incubated with 10 µM CuBOT1 In related work, Ivanović-Burmazović and co-workers showed that sodium nitroprusside (Na 2 [Fe(CN) 5 (NO)]; SNP) reacts in live cells to produce HNO. 18 In this study, the authors employed CuBOT1-loaded HUVECs to show that treatment of these cells with either SNP or H 2 S alone did not elicit a significant fluorescence turn-on.…”
Section: Biological Applications Of Cubot1mentioning
confidence: 99%